Seismic performance of exoskeleton structures. (1st November 2019) - Reggio, Anna; Restuccia, Luciana; Martelli, Lucrezia; Ferro, Giuseppe Andrea
Highlights: Performance of exoskeleton structures as structural control systems under seismic loading. Rigid coupling between the primary structure and the exoskeleton structure. The dynamic behaviour of the coupled system is characterised in frequency domain. RC frame connected to steel diagrid-like exoskeleton structure discussed as case study. Displacement, deformation and internal force control obtained for the primary structure. Abstract: Biomimetic exoskeleton structures are external self-supporting structural systems suitably connected to primary inner structures, the latter being enhanced or protected, in a general sense, by virtue of this connection. Their potential asset for an integrated retrofitting approach, combining structural safety and sustainability merit, has recently drawn considerable attention. In this work, the focus is on investigating the performance of exoskeleton structures as structural control systems under seismic loading. The exoskeleton structure is modelled as a dynamic system whose mass (in principle, not negligible), stiffness and damping properties can be varied and, possibly, designed with the aim of controlling the response of the primary structure. A non-dissipative, and in particular rigid, coupling is assumed between the primary structure and the exoskeleton structure. A first insight into the dynamic behaviour of the coupled system is gained in frequency domain. The dynamic equilibrium is set in non-dimensional form and the response to harmonic base motion is analysed with varying system parameters. Complex-valued Frequency Response Functions are used as performance evaluators in terms of relative displacement, absolute acceleration and transmitted force. A case study is subsequently discussed, dealing with the seismic response of a mid-rise reinforced concrete frame, designed with non-ductile behaviour, coupled to a steel diagrid-like lattice exoskeleton structure. Results of the seismic analyses show that the rigid coupling to the exoskeleton structure allows one to achieve a significant displacement and deformation control of the primary structure, as well as important reductions of its internal forces, in terms of both base and floor shear forces.